Evaluating the role of Demodex infestation and meibomian gland dysfunction in recurrent corneal erosion syndrome - Niu, Xiaoguang; Wu, Shujuan; Xia, Guimei; Xu, Man (Scientific reports, 2024)
This investigation aims to observe the effects of demodex infection and meibomian gland function in recurrent corneal erosion syndrome (RCES), as well as the efficacy of intense pulsed light (IPL) in treating RCES. The study enrolled thirty patients diagnosed with RCES (30 eyes) alongside a control group of thirty-one individuals (31 eyes). Both cohorts underwent a series of diagnostic evaluations, including eyelash sampling, Demodex mite enumeration, infrared imaging of the meibomian glands, and blepharolipin scoring. The RCES subjects were further categorized into two subgroups upon stabilization for comparative analysis of treatment outcomes: the RCES-A subgroup received IPL therapy (16 patients), and the RCES-B subgroup was administered medication treatment (14 patients). Post-treatment, all participants were re-evaluated using the initial diagnostic procedures to monitor for recurrence. Preliminary findings indicated significant differences between the RCES and control groups in terms of meibomian gland scores (4 [3.0, 4.0] vs. 2 [1.0, 3.0]), blepharolipin scores (15.5 [11.0, 16.8] vs. 8.0 [5.5, 10.0]), and lid margin scores (3.0 [2.8, 3.0] vs. 2.0 [1.0, 3.0]), with P < 0.01 for all comparisons. Additionally, the Demodex count was significantly higher in the RCES group (8.0 [4.0,9.0]) compared to the control (0 [0, 2]) (Z = − 4.13, P = 0.00), with a Demodex positivity rate of 83.3% in the RCES group versus 38.7% in the control group (χ2 = 7.60, P < 0.01). Post-treatment, the RCES-A subgroup exhibited significant improvements in meibomian gland loss scores, blepharolipin scores, lid margin abnormality scores, and a reduction in Demodex counts ( P < 0.01), with a post-treatment Demodex positivity rate of 56.3% ( P = 0.11). During the follow-up, the RCES-A subgroup experienced a lower relapse rate compared to the RCES-B subgroup (1 vs. 6 patients). The findings suggest a correlation between meibomian gland dysfunction and Demodex infestation with the incidence of RCES. The application of IPL therapy in combination with meibomian gland massage demonstrates significant potential in enhancing meibomian gland functionality, reducing Demodex counts, and effectively mitigating the recurrence of RCES. Clinical trial registration: https://www.chictr.org.cn/ ChiCTR2000039494 (30/10/2020).